2022
DOI: 10.1186/s12884-022-05121-z
|View full text |Cite
|
Sign up to set email alerts
|

Service readiness and availability of perinatal care in public hospitals - a multi-centric baseline study in Nepal

Abstract: Background Poor quality of maternal and newborn care contributes to nearly two million deaths of mothers and their newborns worldwide annually. Assessment of readiness and availability of perinatal care services in health facilities provides evidence to underlying bottlenecks for improving quality of care. This study aimed to evaluate the readiness and availability of perinatal care services in public hospitals of Nepal using WHO’s health system framework. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Compared to results from NHFS 2015 [ 26 ], the availability of all other signal functions except parenteral oxytocin has decreased at national level which also resembles the findings presented in the annual report of DoHS [ 15 ]. One of the multicentric studies in 2022 has also revealed a considerable gap in neonatal care services which aligns with our study [ 27 ]. The met need of EOC has been continuously declining in the last four fiscal years.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to results from NHFS 2015 [ 26 ], the availability of all other signal functions except parenteral oxytocin has decreased at national level which also resembles the findings presented in the annual report of DoHS [ 15 ]. One of the multicentric studies in 2022 has also revealed a considerable gap in neonatal care services which aligns with our study [ 27 ]. The met need of EOC has been continuously declining in the last four fiscal years.…”
Section: Discussionsupporting
confidence: 90%
“…The finding is consistent with an observational study of four referral level public hospitals in Nepal which found that skin-to-skin contact was practiced in only 3.50% of babies who breathed spontaneously after birth [ 22 ]. The lack of trained and motivated healthcare staff, along with logistical challenges affects its availability [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we purposively selected three districts among the 77 in Senegal- where collaborators had existing partnerships: two rural (Dahra, Kaffrine) and one urban (Pikine) district. The sample size was determined by resources available for the study, as has been described in earlier service readiness studies with sample sizes of between 12 and 30 health facilities [31],[32]. We selected fifteen PHC facilities, five from each district using random number allocation from the sample frame list from the chief medical officer (18 facilities in Dahra, 24 in Kaffrine and 12 in Pikine).…”
Section: Methodsmentioning
confidence: 99%